Eksistensi Muslimah dalam Membangun Peradaban Umat di Kabupaten Enrekang - Sri Ujiana Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The Prophet Muhammad saw. was sent to convey the prophetic treatise from Allah Swt. in order to make Islam a complete and perfect belief, and to protect humanity as rahmatan lil 'alamin. Muslimah Wahdah Region of Enrekang in collaboration with Student Community Service of STIBA Makassar Year of 2022 makes activities for Muslim women and children as a form of existence in restoring Islamic civilization, among these activities are teaching TPA, teaching tahfidz, teaching Arabic, carrying out cycles of memorizing the Qur'an, conducting seminars about Ramadan, and spreading the Qur'an and Ifthor. The Real Work Lecture Program in collaboration with MWD Enrekang can run well even though there are activities that are not carried out.